Modeling of Marketing: A Strategy to Increase Al-Qur’an Education Institutions Image and Students Interests - Ahmad Junaidi; Biyanto Biyanto; Eni Fariyatul Fahyuni (Tarbawi, 2021)
This study explores the marketing model developed, the media used, and effectiveness in enhancing the Al-Qur'an educational institution image and students' interests. This research design is with an observational case study approach. The results showed that marketing modeling was carried out by adopting two marketing models: Offline by involving teachers and students in distributing information verbally to colleagues, relatives, neighbors, and the community, distributing brochures to mosques, educational institutions as well as government and radio and television; and online with WhatsApp, Website, and Instagram media. The implementation of these two marketing models is considered effective in improving the institution image and student interest with evidence of institution popularity as the primary preference for Al-Qur'an education, especially in East Java, the increase of students is relatively significant and stable, the positive response of students to the institution and the relationship between students and institution runs effectively and competently. However, if the effectiveness is compared, according to Ustadz Mukhtar Ismail, offline marking is more effective because a majority of students are adults, and the elderly rarely operating the gadgets. With offline marketing, marketers can more freely explain the institution's products. The primary indicator of developed marketing effectiveness is that the development of new students in each period was 300 to 500 new students.